Harmonização do princípio da proteção com a flexibilização de direitos pela via negociada - Fernandes, Bárbara Barbosa (2021)
The present research proposes to address the harmonization of the protection principle with the prevalence of negotiated over legislated, based on the appreciation of private collective autonomy. From this perspective, in addition to the study of the protective principle, the relevance of collective bargaining for the labor scenario is highlighted, making it clear that, as in individual law, collective law has its own principles to be applied to collective negotiations from which collective agreements and collective conventions are derived. Subsequently, the labor reform is analyzed, as well as the flexibilization of rights through negotiated over legislated rights according to art. 611-A of the CLT, the restriction of negotiated over legislated rights according to art. 611-B of the CLT, as well as the social function of the company, the Fourth Industrial Revolution and the coronavirus pandemic as justifications for the responsible flexibilization of rights. To reach the core of the research, the compatibility of the protection principle is discussed with the flexibilization of rights through negotiation resulting from Law 13,467/2017, when the excess of rigidity of the labor norm is discussed in the face of the new social and economic context we are now experiencing